The Zhuangzi as a Commentary on Kongzi - Sellmann, James D. (Religions, 2024)
The role of Kongzi 孔子, in the Zhuangzi, has been a compelling story. Can we read the stories about Kongzi as constituting a type of commentary on his teachings and the early development of Confucian philosophy in general? First, let us consider the way Zhuangzi has put his own teachings into the mouth of Kongzi because he was accepted to be a sage who understood how to live well. Then, I turn to the more problematic references to Kongzi as being punished in Chapter 5 and his being a “condemned person” in chapter 6 to illustrate how these stories are taken to be forms of commentary or criticism of Kongzi’s project because he did not understand complete virtue. The role of Kongzi in the Zhuangzi can be read as a criticism-like commentary using Kongzi to criticize Kongzi.